Fear of knowledge against relativism and constructivism - Boghossian, Paul Artin (Oxford : Clarendon, 2010)
Paul Boghossian sweeps away relativist claims that there is no such thing as objective truth or knowledge, but only truth or knowledge from a particular perspective. He shows that philosophy provides rock-solid support for common sense against the relativists, and will prove provocative reading throughout the discipline and beyond.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Relativity; Objectivity; Constructivism (Philosophy)